Aeroallergens from Poplar Trees in Kashmir Valley of India - Bhat, GH. Mohiuddin; Singh, Amarjeet; Shazmeen, Qasba; Singh, Ombir (Indian Forester, 2013)
Kashmir valley has been witnessing an increase in allergy disorders due to aeroallergens present in the environment. Aero allergy from Populus deltoids specifically seed menace is the new addition in the list of aeroallergens in valley. The female species of the plant has left the valley sneezing and coughing ever since it started shedding seeds in the months of April and May every year. There is a sudden spurt in lung and throat illnesses, and cold and fever, during these days. The seeds are also allergic to eyes and many schools in Srinagar, capital city of Jammu and Kashmir state, have even prescribed masks to the students. The white fluffy substance - a product of poplar, cover the roads during April/May each year and is often mistaken for sleet or cotton, but go closer and it could trigger instant sneezing, a running nose and throat irritation due to allergens presence. Detail clinical studies are required to test seed menace of poplar on atopic population in the valley. The strategies and precautions to reduce this seed menace are discussed in this article.